Assesmen Psikososial Terhadap Korban Bullying Pada Anak Dengan Down Syndrome - Riefky Aulia; Sri Nurhayati Selian (Jurnal Sultra Elementary School, 2026)
This study aims to examine the psychosocial conditions of children with Down syndrome who are victims of bullying through a comprehensive psychosocial assessment. A qualitative, descriptive approach was used to gain an in-depth understanding of the children's experiences, the forms of bullying they experience, and the resulting impacts. Data were collected through observation, in-depth interviews, and documentation, with the children's families as the primary informants. The results indicate that children experience various forms of bullying, such as verbal and social exclusion, which result in decreased self-confidence, anxiety, and a tendency to withdraw from social circles. Family support has been shown to play a crucial role in helping children cope with these impacts through emotional support and the creation of a safe environment. Furthermore, a less inclusive social environment can exacerbate children's conditions, while a supportive environment can enhance social adaptation. A psychosocial assessment provides a comprehensive picture of a child's condition, helping to accurately identify psychological and social needs. The implications of this study suggest that effective interventions need to be implemented holistically, involving families, schools, and the community. Therefore, this study contributes to the development of support and intervention strategies for children with Down syndrome who are victims of bullying to improve their psychosocial well-being.